Functional feed with Euglena sp.: a novel approach to growth and metabolic health in Rasbora lateristriata - Khusnul Qonita Maghfiroh; Bambang Retnoaji; Arief Budiman; Eko Agus Suyono (Fisheries and Aquatic Sciences)
Elevating blood glucose levels in fish is a common approach employed to assess the efficacy of feed additives in reducing blood sugar. Glucose induction (GI) can induce oxidative stress and metabolic problems in fish, causing damage to their development and health. The potential of Euglena sp. as a microalgal source of bioactive chemicals that enhance health requires additional investigation for its application as a functional feed. Rasbora lateristriata, with significant economic potential, is an appropriate model for this study due to the clear observability of its glucose metabolism response. This study investigates the impact of incorporating Euglena sp. as a dietary supplement on growth performance, digestive histology, and the reduction of body sugar levels. Five experimental diets and treatments were developed in this research: baseline feed (C); basal feed with glucose induction (CN); basal feed with 1% Euglena (E1); basal feed with 1% Euglena and glucose induction (GIE1); and basal feed with 2% Euglena and glucose induction (GIE2). The results indicate that Euglena sp. feed can enhance growth performance by improving digestive efficiency and mitigating metabolic stress. The E1 treatment yielded the maximum growth in terms of weight gain (WG), specific growth rate (SGR), and ultimate length, with values of 46.67 ± 0.17% (seven times the control), 2.08 ± 0.08 (seven times the control), and 53.67 ± 2.17 mm, which is 19% more than the control. The following ranking includes GIE1 and GIE2, both GI treatments that induce metabolic stress; however, they yield excellent results compared to the control group when Euglena sp. is incorporated. The intestinal histology showed the best results in treatment, with Euglena sp. being added as E1, GIE1, and GIE2, which had absorbance areas of 81,403.32 µm2, 66,622.22 µm2, and 51,166.50 µm2, respectively. The GIE1 treatment led to the greatest reduction in blood sugar, with GIE2 following closely behind. Furthermore, Euglena sp. shows promise as a functional feed by increasing growth rates, improving digestion, lowering blood glucose levels, and speeding up the recovery from metabolic stress in living things. This suggests that it should be studied more for possible future uses.